2011
DOI: 10.1667/rr2605.1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to16O-Particle Radiation Causes Aging-Like Decrements in Rats through Increased Oxidative Stress, Inflammation and Loss of Autophagy

Abstract: Exposing young rats to particles of high energy and charge (HZE particles), a ground-based model for exposure to cosmic rays, enhances indices of oxidative stress and inflammation, disrupts the functioning of neuronal communication, and alters cognitive behaviors. Even though exposure to HZE particles occurs at low fluence rates, the cumulative effects of long-term exposure result in molecular changes similar to those seen in aged animals. In the present study, we assessed markers of autophagy, a dynamic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 42 publications
2
45
0
Order By: Relevance
“…It is generally observed that improving clearance with the induction of autophagy [10,106] or proteasome activity [107,108] slows down the ageing process and improves cognitive functions. Moreover, it was shown that reduced autophagy causes ageing-like decrements [109,110] and facilitates the development of neurodegenerative diseases [111]. Not surprising therefore that induction of autophagy was intensively tested in various models of neurodegenerative diseases.…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%
“…It is generally observed that improving clearance with the induction of autophagy [10,106] or proteasome activity [107,108] slows down the ageing process and improves cognitive functions. Moreover, it was shown that reduced autophagy causes ageing-like decrements [109,110] and facilitates the development of neurodegenerative diseases [111]. Not surprising therefore that induction of autophagy was intensively tested in various models of neurodegenerative diseases.…”
Section: Processes Contributing To Brain Ageingmentioning
confidence: 99%
“…Autophagy is a well-regulated lysosomal degradation process whose disruption, which leads to neuronal dystrophy and death, is a potential mechanism of the aging process and the development of neurodegenerative diseases (Meijer and Codogno 2006;Rajawat et al 2009). Neuroinflammation has been identified as a cause of autophagal dysregulation in aged rats (Poulose et al 2011). Therefore, a potentially valuable approach to combat age-related deficits in behavior is to alter inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Exposing rats to 56 Fe particles has been shown to interfere with spatial learning and memory in the Morris water maze and is correlated with decreased hippocampal neurogenesis (Casadesus et al, 2005;Rola et al, 2004). Studies have also shown that exposing young animals to HZE particle radiation results in "accelerated aging" (Joseph et al, 1992;Poulose et al, 2011), a process where young animals exhibit behavioral and molecular changes similar to that of aged animals. Most of the studies support the role of OS and inflammation as mediators of the deficits observed in neuronal and cognitive functioning following exposure to HZE radiation; however, recent studies conclude that HZE radiation not only causes OS and inflammation, but also alters protective signaling, thereby unleashing a cascade of detrimental signals which ultimately leads to the death of neurons (Cherry et al, 2012;Huang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One contributing molecular factor leading to a decrement in brain performance may be an increase in intracellular toxic proteins due to a failure of macroautophagy following exposure to HZE particles (Poulose et al, 2011). Autophagy is a wellregulated lysosomal process by which intracellular damaged toxic structures, such as protein/lipid complexes, protein oligomers/aggregates and cellular organelles, are identified, sequestered and/or recycled (Friedman et al, 2012;Komatsu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation